Investigation of the relationship between oral motor feeding development and gross motor development between preterm and term infants at 10- to 12-month postnatal age - Erkan Erol; Umut Apaydın; Numan Demir; Bülent Elbasan (SpringerOpen, 2023)
Abstract Background Immature central nervous system, extended stay in the neonatal intensive care unit, and sensory experience deficiency may contribute to oral and gross motor delay in preterm infants. Current study aimed to investigate oral and motor development in preterm infants. Methods Twenty-nine preterm infants and 28 term infants were evaluated within the scope of the study. Oral motor feeding development was assessed with the Schedule for Oral Motor Assessment, and motor development was evaluated with the Alberta Infant Motor Scale. All analyses were performed using SPSS 22. The study was approved by the Gazi University Clinical Researches Ethics Committee (no: 25901600-23). Results There was a correlation between the Schedule for Oral Motor Assessment categories (solid, semisolid, cracker, puree, bottle, and cup) and the Alberta Infant Motor Scale score (p < 0.05). There was a significant difference between groups in the Schedule for Oral Motor Assessment's solid, semisolid, cracker, and puree categories and total score (p < 0.05). There was a significant difference between groups regarding the Alberta Infant Motor Scale score (p < 0.05). Conclusion Preterm infants come behind their term peers in motor and oral motor feeding performance. These two areas of development can influence each other. For this reason, oral motor feeding problems should be emphasized as well as motor problems in physiotherapy rehabilitation evaluations.